Exploring Organizational Performance : A Multidimensional Construct - Baid, Chandresh; Baid, Devesh; Bhuyan, Aswini Kumar (Prabandhan: Indian Journal of Management, 2024)
Purpose : Organizational performance (OP) is one of the most important topics in management study. Combs et al. (2005) proposed growth, the stock market, and accounting returns as the three elements of OP. Using construct validity research, Hamann et al. (2013) built on the work of Combs et al. to support four-dimensional OP concepts in the US setting. The OP construct was examined in this paper with reference to India. Methodology : Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were conducted to establish construct validity. The NSE 500 companies for the period 2018–2019 financial year were considered for the study. Findings : Our results supported an OP model with four dimensions as proposed by Hamann et al. (2013): growth, profitability, liquidity, and stock market measures. We also proposed OP as a second-order reflective formative concept and used PLS-SEM to assess it. Practical Implications : The scholars that examined variance in the OP in an Indian context could now adopt a validated four-dimensional model of the OP construct. The profitability, liquidity, growth, and stock market performance constructs are to be considered while evaluating firm performance. Originality : This study proposed a higher-order construct for OP along with extending Hamann et al.’s (2013) work in the Indian context.